Resistance Mechanisms of Anti-PD1/PDL1 Therapy in Solid Tumors - Lei, Qingyang; Wang, Dan; Sun, Kai; Wang, Liping; Zhang, Yi (Frontiers in Cell and Developmental Biology, 2020)
In cancer-immunity cycle, the immune checkpoint PD1 and its ligand PDL1 act as accomplices to help tumors resist to immunity-induced apoptosis and promote tumor progression. Immunotherapy targeting PD1/PDL1 axis can effectively block its pro-tumor activity. Anti-PD1/PDL1 therapy has achieved great success in the past decade. However, only a subset of patients showed clinical responses. Most of the patients can not benefit from anti-PD1/PDL1 therapy. Furthermore, a large group of responders would develop acquired resistance after initial responses. Therefore, understanding the mechanisms of resistance is necessary for improving anti-PD1/PDL1 efficacy. Currently, researchers have identified primary resistance mechanisms which include insufficient tumor immunogenicity, disfunction of MHCs, irreversible T cell exhaustion, primary resistance to IFN-γ signaling and immunosuppressive microenvironment. Some oncogenic signaling pathways also contribute to the primary resistance. Under the pressure applied by anti-PD1/PDL1 therapy, tumors experience immunoediting and preserve beneficial mutations, upregulate the compensatory inhibitory signaling and induce re-exhaustion of T cells, all of which may attenuate the durability of the therapy. Here we explore the underlying mechanisms in detail, review biomarkers that help identifying responders among patients and discuss the strategies that may relieve the anti-PD1/PDL1 resistance.